L-lysine and dietary fiber improve the physicochemical properties of sausage without added phosphate and reduced salt levels - Junior, Carlos Alberto Alves [UNESP]; Bellucci, Elisa Rafaela Bonadio [UNESP]; Dos Santos, João Marcos [UNESP]; Bertuci, Marcello Lima [UNESP]; da Silva Barretto, Andrea Carla [UNESP] (FapUNIFESP (SciELO), 2023)
The demand for clean label foods has driven research in the meat product sector. The objective of this study was to evaluate the effect on the physicochemical properties of adding L-lysine, wheat fiber (WTF) and microcrystalline cellulose (MCC) in sausage without the addition of sodium tripolyphosphate (STPP) and with reduced salt levels. Eight treatments were produced in total. Three control treatments were: CON1-0.5 % sodium tripolyphosphate and 2 % salt; CON2-without STPP and 2 % salt; CON3-without STPP and 1 % salt. Five other treatments were carried out without STPP and 1 % of salt: LYS-0.8 % L-lysine; WTF-2 % wheat fiber; MCC-2 % microcrystalline cellulose fiber; LYSWTF-0.8 % L-lysine and 2 % wheat fiber; LYSMCC-0.8 % L-lysine and 2 % microcrystalline cellulose fiber. L-lysine and wheat fiber provided good emulsion stability for sausages. L-lysine and MCC increased the yield of the products. Microcrystalline cellulose increased the red color value (a*) of sausages. The intensity of the yellow color value (b*) was significantly affected by the removal of STPP and the reduction of salt levels, but L-lysine and MCC improved this parameter, providing similar results to CON1. Adding of L-lysine and dietary fiber increased hardness in sausages without added STPP and with salt reduction. L-lysine and wheat fiber are promising for reformulating emulsified meat product without phosphate added and with reduced salt levels due to lipid oxidation control and improvement in emulsion stability.
Keywords: amino acid; clean label; microcrystalline cellulose; wheat fiber